The determinants of growth in small and medium enterprises: an empirical study in the logistics industry in Hong Kong - Cheng, Raymond Wai Man (Curtin University, 2006)
Small and Medium Enterprise (SMEs) have contributed significantly to the economic growth of Hong Kong and it is worth investigating how they prosper. This study was based on an examination of a sample of SMEs in the logistics industry operating during the economic crisis in Hong Kong. The factors influencing the growth of small firms are many, complex and erratic. The primary objective of this study was to test the determinants of SME growth. The research question addressed was how and to what extent the characteristics of the owner-manger, the nature of the firm, and company strategy, together with the economic and government factors, impact upon the growth of small business. This study was conducted in 2004, based on a survey of 102 SMEs within the logistics industry in Hong Kong SAR. By studying the factors contributing to the growth of SMEs, this research investigated and analyzed the characteristics of SMEs which were at least three years old during of the period 1998 - 2003. The appropriateness and the support of the determinants that affect SME growth were empirically analysed. The research design was quantitative in nature, testing various hypotheses and theories about the associations between perceived constructs. Outcomes were then compared with factual indicator data, subjected to multiple regression analysis and co-efficiency analysis. The results of the regression analysis showed no tremendous incongruity compared to research conducted in previous studies, although there were some factors associated significantly and some factors associated positively but insignificantly with firm growth. Even though some findings appeared to be inconsistent with previous studies, the preoccupation of researchers and policy-makers worldwide with matters relating to SME growth was recognized.These empirical findings provide evidence that owner-managers may adopt different managerial styles and strategies as a consequence of the amount of growth desired, and the amount of risk they are willing to assume. Of the four main factors identified as influencing the growth of small firms - the characteristics of the owner-manager, the nature of the firm itself, the business strategies adopted, and the external factors concerned - all these four components need to be combined appropriately for growth to be achieved. This means that it is very difficult to identify whether or not a firm will be a success or a failure. The significances of these factors and their impacts have been addressed and reported in the study. Recommendations are made for business practitioners who are still trading, distinguishing between businesses with high and low growth expectations. Owner-managers are encouraged to acquire better management skills and qualifications to improve their managerial capabilities and experience. Appropriate strategic planning, technology advancement, education, training and government support are recommended for improving growth performance. In recognition of the need to improve small business growth, these research findings reveal that some of the factors considered important to success in Hong Kong small businesses are unique to the Hong Kong business environment. In this sense, the findings provide good references for scholars and policy-makers to design policies and provide assistance that are appropriate for use particularly in Hong Kong. Future research directions have been discussed and managerial implications for both practitioners and researchers have been suggested.